CATCH OF COMPOSITION BASED ON THE TYPE, WEIGHT AND LENGTH OF FISH IN THE DRIFT GILLNET FISHING GEAR WITH DIFFERENT MESH SIZE (CASES OF STUDY IN MESKOM VILLAGE, BENGKALIS SUBDISTRICT, BENGKALIS REGENCY, RIAU PROVINCE) - Sofia Marwani; Bustari Bustari; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was conducted in February in the Meskom village, Bengkalis subdistrict, Bengkalis regency, Riau province. The purpose of this research was to determine the effect and differences in catches of drift gillnet by using the mesh size differences. The method used is a survey method. Catches of drift gillnet with 2 inch mesh size are Bombay duck, Slender shad, Shorthead hairfin anchovy, Sagor catfish, Shark and White pomfret. Based on the total weight obtained, the catch was dominated by Shorthead hairfin anchovy (setipinna breviceps) by 30% with a total weight of 89,5 kg.The catch in the mesh size of 3 Inches is not as much as the mesh size of 3 Inch, namely Wolf herrings, Tread Fins, Narrow barred spanish mackerels and Longjaw thryssa. The percentage of catch that was dominated was Tread fins. From the t-test calculation, there is a difference in the catch of the drift gillnet. Keyword: Drift Gillnet, Mesh Size, Catch